Effect of drying method on supercritical CO2 extraction of grape seed oil - Jakobović, Mario (Array, 2019)
Aim of this study was to monitor the influence of drying method (naturally and chamber drying) and different sample preparation on supercritical CO2 extraction of oil from three grape seed varieties (Graševina, Zweigelt, Cabernet Sauvignon). The highest oil content was obtained from naturally dried screened and washed seeds of red variety Cabernet Sauvignon (14.85%) and lowest from chamber dried screened seeds of white variety Graševina (7.67%). Peroxide value ranged from 0.36 to 1.77 mmol O2/kg oil, free fatty acids 0.28-8.0%, and insoluble impurities 0.05-0.28%. Determined fatty acids were palmitic (6.98-11.58%), stearic (3.82-6.59%), oleic (14.90-19.97%) and linoleic acid (61.82-71.96%) in oil obtained from naturally dried seeds and 6.84-8.68%, 4.12-5.73%, 15.10-20.18% and 67.88-70.76% in oil from chamber dried seeds, respectively. In defatted cakes after supercritical CO2 extraction, protein and fibre content ranged from 8.17 to 9.85% and 34.58 to 43.96%, respectively. According to ANOVA results, sample preparation and drying method had statistically significant influence on grape seed oil extraction.